Identification of Leptospira Bacteria in Human Urine According to Islamic View - Satryanto, Muslimin Budiman; Widiyanti, Dian; Karimulloh, Karimulloh (Jurnal Medis Islam Internasional, 2020)
Leptospirosis is a zoonotic infectious disease caused by pathogenic organisms belong to the genus Leptospira, which are transmitted directly or indirectly from animals to humans. Most countries in the Southeast Asia regions are endemic for leptospirosis. The incidence of leptospirosis is strongly influenced by various socio-cultural, occupational, behavioral, and environmental factors. The amount of risk depends on the prevalence of Leptospira in the local area and the frequency of exposure. One of the tests to confirm the diagnosis of leptospirosis is by isolating Leptospira bacteria with culture and molecular examination of a person's body fluid specimens such as blood, cerebrospinal fluid, or urine. To identify Leptospira bacteria in leptospirosis cases in humans, urine samples can be used. This examination is the development of methods used in medical science to diagnose leptospirosis. One of the verses in the Qur’an regarding science is "He is the One Who created everything in the earth for you. Then He turned towards the heaven, forming it into seven heavens. And He has ˹perfect˺ knowledge of all things.” (Surah Al-Baqarah [2]: 29). From this verse, it can be concluded that Allah SWT created something on this earth, including urine in it, with the intent and purpose for all of His creation, so that his servants understand and worship Allah SWT and carry out their obligations as caliphs on this earth. According to the Islamic view, identification of Leptospira bacteria in the urine of workers is permissible because science and religion are related.